Enhance Parameter Speed Estimation of Induction Motor Using Modified Voltage Model Flux Estimation - Solly Aryza; zulkarnain lubis (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
Enhance Parameter Speed Estimation of Induction Motor Using Modified Voltage Model Flux Estimation